Pengaruh Lagu ”Satu Bulan” : terhadap Perubahan Emosi dan Harapan dalam Melodi Bernadya - Adam Zamzam Putra Setiawan; Nasywa Aulia Khaerunissa; Sri Mulyeni (Jurnal Bersama Ilmu Pendidikan (DIDIK), 2025)
Music is one of the most commonly used forms of communication and is enjoyed by various segments of society. The emotions contained in music certainly have a significant impact on the physiological state of the listener, and even the hopes embedded in a piece of music can greatly influence a persons outlook on life. The research on the influence of the song “Satu Bulan” aims to demonstrate how music can change a person’s emotions and hopes. A total of 30 repondents, consisting of Management students from Universitas Nasional PASIM, participate in this experiment. The method used in this research was a pre-test to measure their emotions before listening to the song “Satu Bulan” followed by a post-test to assess their emotions after listening to the song. The pre-test results show that 22 people or 67% feel happy, 7 people or 20% feel sad, and 1 person or 3% feels angry. The post-test results show that 3 people or 9% still feel happy, 26 people or 88% have become sad or become sadder, and 1 person or 3% still feels angry or becomes angrier. The results of this study reveal that 91% of the 30 respondents experienced an emotional change, which indicates that the change towards sadness is high. Kata Kunci: Emosi, Musik, Harapan, Mahasiswa